Effect of Approach Distance and Change of Direction Angles Upon Step and Joint Kinematics, Peak Muscle Activation, and Change of Direction Performance - Falch, Hallvard Nygaard; Rædergård, Håvard Guldteig; van den Tillaar, Roland (Frontiers in Sports and Active Living, 2020)
The aim of the study was to compare the step kinematics, joint angles, and muscle activations between change of direction (COD) maneuvers with different angles and approach distances, suggested to require different strength and velocity demands. Twenty-three male soccer players completed eight COD tests consisting of both 4 and 20-m sprint approaches with one directional change which varied between each COD test (45, 90, 135, and 180°). Peak muscle activity, step and joint kinematics of the lower limbs of the plant, and re-acceleration step were measured. Compared to 4-m CODs, the 20-m COD approach distances increased vertical center of mass displacement (p < 0.001), number of deceleration steps (p < 0.001), revealing no statistical differences upon joint angles (p > 0.05). Greater COD angles resulted in increased ankle dorsiflexion, hip abduction and flexion, greater displacement of the center of mass and tibia angle, longer contact times, and more deceleration steps (p < 0.034). The CODs categorized as velocity-dominant revealed higher peak muscle activity in the adductor longus, semitendinosus, biceps femoris, and gastrocnemius. It was concluded that velocity-dominant CODs revealed higher muscle activity due to a higher eccentric loading, implicating task-specific training considerations for enhancing COD performance.